Characteristics of blood lactate removal during competition in young swimmers - Chainok, P.; Tongnillpant, N.; Sripakdee, S.; Zacca, R.; Fernandes, R. J.; Vilas-Boas, J. P. (XIII th International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2018)
The aim of this study was to assess the characteristics of self-selected active strategies and rate of lactate removal corresponding to difference training phases upon repeated measures. The [La-] values 3 min after swimming events and at the end of active recovery were obtained from 30 swimmers (14 males and 16 females; 13-18 years old) for two years (319 swimming races). The volumes of active recovery in each swimming event ranged between 800-1400 m. Distance of each active recovery segment, time and swimming speed achieved following recovery period were recorded. Analysis of variance for repeated measurements was applied comparing [La-], distance, speed and [La-] removal related to training period in each swimming distance. Mean active recovery swimming speed were 0.90 ± 0.12, 0.87 ± 0.10, 0.92 ± 0.11, 0.91 ± 0.07, 0.82 ± 0.06 and 0.82 ± 0.05 m/s for 50-, 100-, 200-, 400-, 800- and 1500-m (60.45 ± 9.97% of average swimming speed in each event). [La-] after recovery periods for 50-, 100-, 200-, 400-, 800- and 1500-m were 2.37 ± 1.22, 2.52 ± 0.68, 2.63 ± 0.70, 2.47 ± 0.87, 2.07 ± 0.61 and 2.40 ± 0.71 mmol/L. Distance and time of active recovery showed inverted U-shaped profile with the highest value in 400-m. The [La-] and [La-] removal were lowest in the preparation period (6.53 ± 2.11 and 2.39 ± 0.64 mmol/L) and highest in the competition period (9.44 ± 3.19 and 2.98 ± 1.10 mmol/L. These results suggest that there is an optimal active recovery (volume vs speed) in which young swimmers and coaches should be aware.